Intranasal exposure to manganese disrupts neurotransmitter release from glutamatergic synapses in the central nervous system in vivo - Moberly, Andrew H. (2012)
Chronic exposure to aerosolized manganese induces a neurological disorder that includes extrapyramidal motor symptoms and cognitive impairment. Inhaled manganese can bypass the blood-brain barrier and reach the central nervous system by transport down the olfactory nerve to the brain’s olfactory bulb. However, the mechanism by which Mn disrupts neural function remains unclear. Here we used optical imaging techniques to visualize exocytosis in olfactory nerve terminals in vivo in the mouse olfactory bulb. Acute Mn exposure via intranasal instillation of 2–200 μg MnCl(2) solution caused a dose-dependent reduction in odorant-evoked neurotransmitter release, with significant effects at as little as 2 μg MnCl(2) and a 90% reduction compared to vehicle controls with a 200 μg exposure. This reduction was also observed in response to direct electrical stimulation of the olfactory nerve layer in the olfactory bulb, demonstrating that Mn’s action is occurring centrally, not peripherally. This is the first direct evidence that Mn intoxication can disrupt neurotransmitter release, and is consistent with previous work suggesting that chronic Mn exposure limits amphetamine-induced dopamine increases in the basal ganglia despite normal levels of dopamine synthesis (Guilarte et al., J Neurochem 2008). The commonality of Mn’s action between glutamatergic neurons in the olfactory bulb and dopaminergic neurons in the basal ganglia suggests that a disruption of neurotransmitter release may be a general consequence wherever Mn accumulates in the brain and could underlie its pleiotropic effects.